Le flirt à Rabat au Maroc : Engagements des corps et arrangements socio-spatiaux - Chadia Arab; Christophe Guibert (L’Année du Maghreb)
In Morocco, the possibility of flirting in the public space is evident in many ways. However, heterosexual seduction practices in Morocco are not to be taken for granted in a country where bodies, especially women’s bodies, are subject to strong political and social control. Our article intends to break with the dominant discourses and ethnocentric visions, in Morocco as in France, which consider sexualities in Morocco only through the prism of religion and women’s passivity. This article deals specifically with issues of power and bodies in the public space : what is possible and what is not. Our analysis focuses on unmarried Moroccan heterosexual couples. It is drawn from exploratory surveys (non-participant observations in selected locations during several consecutive days and 15 semi-structured interviews with Moroccan couples) conducted in April 2016 in Rabat, the country’s administrative capital. According to the results of our qualitative survey, the ways of flirting before marriage, potentially reprehensible in the eyes of society, are quite homogeneous. The article shows that young women and men innovate in terms of strategies for living out their expressions of intimacy through what we have called “geographical bubble”. These bubbles, identified beforehand, constitute places that both protect them from indiscreet and reproachful eyes and allow for intimacy. Couples, and especially women, pay crucial attention to the choice of locations for their romantic encounters : they want to avoid being seen, while remaining safe to flirt. The article is organized in two parts. The first presents the restrictive legal and moral framework of sexuality in Morocco, while highlighting a recent dynamic of social and sexual transition. This transition is eminently linked to the publicization of issues of individual and sexual freedom, the emergence of which has made it possible to debate the sexuality of Moroccan men and women, helping to normalize it and make it legitimate whether it is expressed within or outside of marriage. The second part of the paper focuses more specifically on two locations of the survey. The Printemps café, a “geographical bubble” in the heart of downtown Rabat, offers a private space open to the public where young couples are very present, much more so than elsewhere in the city, and allows flirting. The cornices and beaches are also places where young couples can meet, away from prying eyes, as shown in the photographs that illustrate the article. The couples behave like “teams”, as Erving Goffman (1973) formulates it, operating jointly a strict control of their gestures, representations, body distances and finally of the glances coming from outside. Complicity within the couple therefore, but also between couples in the same place. These precautions underlie the existence of these “geographical bubbles” and of flirting within them, at a distance from the control of the authorities : the intimate and individual experiences are thus also revealed to be a group practice and conceived with regard to the group. The “geographical bubbles” thus make it possible to preserve the respectability of young women (especially) within families and to avoid the mechanisms of exclusion and marginalization. In the end, they are evidence of territorialized practices that contribute, even if modestly, to questioning dominant heteronormative behaviors. The couples met during the survey, by their mere presence in the public space, participate in the deconstruction of institutional gender behaviors and thus in a localized process of gender mixing.